Impact of equity in social protection spending on income poverty and inequality - Daria Popova (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
This study aims to investigate whether higher equity in government social protection spending strongly predicts positive changes in income poverty and inequality. Our approach was to regress the measures of absolute poverty and inequality on the indicators of equity in social protection spending at the country level, controlling for the level of spending and the country wealth measured by per capita GDP. For that purpose, we have compiled a dataset of 535 observations from 101 countries over years 1998–2017, including 199 observations for 70 low- and middle-income countries from Europe, Asia, North and South America, and Africa. Our findings support the proposition that equity in social spending (measured by the share of social protection spending going to the bottom quintile) is a significant and strong predictor of improved distributional outcomes (poverty measured at Int1.90 a day and inequality measured by the Gini index). Moreover, in low- and middle-income countries in our sample the poverty and inequality reducing impact of this equity measure is stronger than in the sample including all countries. The presence of a significant gap in equity of social protection spending between the high-income countries and the rest of countries included in the study signifies that there is a large potential in improving equity in social protection spending in low- and middle-income countries. Social protection reforms in these countries should be focused on extending the coverage of social protection programs and improving access to social protection for the poorest segments of the population.
Keywords: 330; Income Dynamics; Poverty; Welfare Benefits; Economics; Public Policy